Ribaltare lo sguardo forensic architecture tra arte, estetica e tecnologia - Garavello, Christian Vittorio Maria (Mechane, 2025)
The essay focuses on the relationship between the practice of investigative agency Forensic Architecture established at Goldsmith College in London in 2010 by architect and theorist Eyal Weizman with artists, architects, journalists, jourists and others, and several artistic practices founded on the social and political impact of technologies. The pivotal concept of agency’s practice is counterforensic, the aim is to turn the forensic gaze, usually oriented from state to citizens, to monitor the states, armies and big companies’ criminal actions.Technology development plays a central role in this context, on the one hand gives power and allow a complete access to sensibile data and images, to states, armies, corporations to control citizens, but on the other hand gives a chance to citizens, ONG, independent researchers like Forenisc Architecture to control their operations.Forenisc Architecture looks at technology tools as a chance to support civil and oppressed people causes. In this context art plays a central role and the essay shows the relationship and the impact of Allan Sekula, Harun Farocki and Lawrence Abu Hamdan’s practices have had on Forenisc Architecture practice.